High Mobility Group Box 1 (HMGB1) Induces Toll-Like Receptor 4-Mediated Production of the Immunosuppressive Protein Galectin-9 in Human Cancer Cells - Teo Hansen Selnø, Anette; Schlichtner, Stephanie; Yasinska, Inna M.; Sakhnevych, Svetlana S.; Fiedler, Walter; Wellbrock, Jasmin; Berger, Steffen M.; Klenova, Elena; Gibbs, Bernhard F.; Fasler-Kan, Elizaveta; Sumbayev, Vadim V. (Frontiers in Immunology, 2021)
High mobility group box 1 (HMGB1) is a non-histone protein which is predominantly localised in the cell nucleus. However, stressed, dying, injured or dead cells can release this protein into the extracellular matrix passively. In addition, HMGB1 release was observed in cancer and immune cells where this process can be triggered by various endogenous as well as exogenous stimuli. Importantly, released HMGB1 acts as so called “danger signal” and could impact the ability of cancer cells to escape host immune surveillance. However, the molecular mechanisms underlying the functional role of HMGB1 in determining the capability of human cancer cells to evade immune attack remain unclear. Here we report that the involvement of HMGB1 in anti-cancer immune evasion is determined by Toll-like receptor (TLR) 4, which recognises HMGB1 as a ligand. We found that HGMB1 induces TLR4-mediated production of transforming growth factor beta type 1 (TGF-β), displaying autocrine/paracrine activities. TGF-β induces production of immunosuppressive protein galectin-9 in cancer cells. In TLR4-positive cancer cells, HMGB1 triggers formation of an autocrine loop which induces galectin-9 expression. In malignant cells lacking TLR4, the same effect could be triggered by HMGB1 indirectly through TLR4 expressing myeloid cells present in the tumour microenvironment (e. g. tumour-associated macrophages).